The role of certain mortality factors in the underperformance of Aristaea (Parectopa) thalassias (Meyrick) as a biological control agent of Leptospermum laevigatum F. Muel. - Mlokoti, Thembelihle (Department of Biological Sciences, 2022)
Leptospermum laevigatum is indigenous to the coasts of south and central New South Wales in Australia. It has become invasive in South Africa since its introduction in the 1800s, competing with the native fynbos across the coastal regions of the Western Province and into the Eastern Cape Province. Due to its aggressive spread, it became a significant concern and is considered a highly invasive species requiring a concerted management plan in South Africa. Biological control of L. laevigatum has been implemented since the 1980s with limited success to date. Aristaea (Parectopa) thalassias is one of two biological control agents introduced against L. laevigatum and is present across the plant's distribution along the coastal regions of the Western Cape Province and into the Eastern Cape Province in South Africa. In order to understand the limited success of A. thalassias, this study considers the biology of the immature stages, larval mortality due to parasitoids, predation and overcrowding, and seasonal influences on development and survival. The findings showed that A. thalassias is present throughout the year, completes its life cycle in 58 days (as measured in spring), and thus has the potential to complete several overlapping generations throughout the year. Levels of overall mortality of larvae, pre-pupae and pupae averaged over a 20-month period indicated seasonal variability, with highest mortality in autumn and winter. Mortality attributed to parasitism was highest in summer (maximum 25% in one year). Furthermore, predation and overcrowding (maximum 15%) were also low, and thus these mortality factors are unlikely to account for the low efficacy of the agent. Despite this, mortality through other unknown factors was at times found to be high, especially for first instar larvae in mined leaves (maximum 58% in one year). The peak oviposition period was not aligned with the peak in production of new leaves, suggesting a possible phenological mismatch between L. laevigatum and its biological control agent A. thalassias which could curb population expansion. Whilst mortality resulting from unknown factors (i.e., not investigated in the scope of this study) might be playing an important role in the performance of A. thalassias, specific factors investigated during this study could not explain why the moth is not more prolific. Determining why any particular biological control agent is ineffective is often not a straightforward exercise because it may be the result of a complex of interacting factors, which are not easily discernible. The findings of this study show that this is probably true for A. thalassias in South Africa and much more work is needed to resolve the reasons for its underperformance as a biological control agent.